Situational Leadership Theory and Staff Performance: A qualitative cross-sectional study, making use of in-depth interviews, describing the perceptions of Leaders on staff performance within the Durban’s Private Hospitals - van der Hoven, Walter (The IIE, 2018)
The South African Healthcare sector is faced by many Leadership Challenges. Gray, Vawda, Padarath, King, Mackie & Casciola, (2016) identified a lack of efficiency in the South African Healthcare workforce which has a disabling effect on the health of the nation. Additionally, the Future Health Index (2017) analysed 19 countries Healthcare sectors and scored South Africa as the lowest in terms of efficiency. This cross-sectional qualitative study that was guided by the Paul Hersey and Ken Blanchard’s 1972 Situational Leadership theory; and used in-depth interviews to collect data from four of Durban’s Private Hospital Managers identified through purposive sampling and then qualitative content analysis was used in order to analyse the data. The purpose of this interpretivist study was to gain an in-depth understanding of the staff performance as perceived by Hospital Managers in Private Hospitals in Durban. The researcher believes that the study could contribute to further studies aimed at solving Healthcare’s efficiency related Leadership Challenges. The findings of study found that Private Hospital staff showed poor performance, lack of dedication to duty, were resistance to change, and unwilling to learn new skills. Furthermore, themes relating to Leadership strategies were also were identified, these were: that Private Hospital Managers show recognition to deserving staff they provide constructive staff feedback and training, provide encouragement and promoted teamwork. Healthcare’s leadership also believed that “enthusiasm” was important trait for employees to have so they learned skills quickly.
Keywords: Situational Leadership Theory; private hospitals; staff performance; perceptions of leaders; Healthcare workforce